The Impact of Organizational Culture, Work Discipline, and Facilities on The Work Productivity - Nurdiansyah, Fahrizal; Widodo, Zandra Dwanita; Darsono, Darsono (Forum Kerjasama Pendidikan Tinggi, 2025)
Productivity is the ability of employees to complete tasks according to standards, costs, completeness, and speed, reflecting the efficiency and effectiveness of human resources. This study aims to analyze the impact of (1) Organizational Culture, (2) Work Discipline, and (3) Facilities on Employee Productivity at the Boyolali District Office, both partially and simultaneously. This research is quantitative in nature and uses primary data. Data quality testing was conducted through validity and reliability tests. The methods used include observation and questionnaire distribution. From a total population of 18 individuals, all were selected as samples using the saturated sampling technique. Data analysis was performed using multiple linear regression. The study's results indicate that Organizational Culture partially impacts Employee Productivity by 24.5%, Work Discipline by 28.9%, and Facilities by 28.3%. Simultaneously, these three variables significantly affect Employee Productivity, with a significance value of 0.000 < 0.05. The coefficient of determination reveals that 73.4% of the variation in Employee Productivity can be explained by Organizational Culture, Work Discipline, and Facilities, while the remaining 26.6% is influenced by other variables not examined in this study.